Capsular phimosis with complete occlusion of the anterior capsular opening after intact continuous curvilinear capsulorrhexis - Al-Kharashi, Soliman A. (Elsevier, 2009)
Shrinkage and whitening of the anterior capsule opening – capsular contraction syndrome – is a well-known complication after continuous curvilinear capsulorrhexis. A 72-year-old women underwent continuous curvilinear capsulorrhexis, phacoemulsification, and implantation of posterior chamber intraocular lens with polymethylmethacrylate haptics. Four months postoperatively, the patient reported deterioration in visual acuity that was resulted due to complete occlusion of anterior capsular opening by fibrotic tissue. The fibrous membrane was excised surgically in capsulorrhexis fashion.